Analysis of blood pressure variability in lacunar and non-lacunar types acute ischemic strokes patients as a predictor of clinical outcomes - Maulida; Akbar, Muhammad; Bahar, Ashari; Masadah, Rina; Tammasse, Jumraini; Kaelan, Cahyono (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Stroke is a well-known global health concern that causes significant mortality and morbidity, with ischemic stroke being the most prevalent kind. The pathogenesis and clinical consequences of various lacunar and non-lacunar subtypes vary from one another. A patient’s clinical fate following an acute ischemic stroke may be predicted by elevated blood pressure variability (BPV). The aim of this study to investigate the association between BPV and functional outcomes in patients with acute ischemic stroke (lacunar and non-lacunar subtypes). Methods: This prospective cohort study categorized patients with acute ischemic stroke as either lacunar or non-lacunar based on non-contrast CT scan results. BPV values were recorded at the onset and at 4 intervals daily for 3 continuous days after the patients were admitted. The modified Rankin Scale (mRS) was used for outcome assessments on the seventh day, classified into good (0-2) and poor outcomes (3-6). Predictive values were determined using ROC analysis. Results: Out of 67 patients, 40.3% had poor outcomes, whereas the other 59.7% had good outcomes. Lacunar stroke was observed to occur more frequently in patients with positive results. The sensitivity and specificity of ROC analysis were disputed, and there was no discernible relationship between systolic and diastolic blood pressure and mRS scores. Conclusions: BPV was not directly linked to functional outcomes, nor was a cut-off value that appears to work consistently established. Better functional outcomes were observed in patients with lacunar stroke, highlighting the prognostic value of using it in the treatment of ischemic stroke.